Benjamin's Passages : Dreaming, Awakening - Gelley, Alexander (Book collections on Project MUSE., 2014)
In transposing the Freudian dream work from the individual subject to the collective, Walter Benjamin projected a ""macroscosmic journey"" of the individual sleeper to ""the dreaming collective, which, through the arcades, communes with its own insides."" Benjamin's effort to transpose the dream phenomenon to the history of a collective remained fragmentary, though it underlies the principle of retrograde temporality, which, it is argued, is central to his idea of history. The ""passages"" are not just the Paris arcades: They refer also to Benjamin's effort to negotiate the labyrinth of his wo.